The effect of group VIII elements on the magnetic and vibrational properties of MnPt alloy: Ab initio study - Diale Ramogohlo; Ngoepe Phuti; Moema Joseph; Chauke Hasani; Phasha Maje (MATEC Web of Conferences)
The magnetic properties of MnPt alloy have attracted much attention due to its potential use in magnetic recording and spintronics. Previous studies have indicated that this alloy retains its antiferromagnetism at room temperature. Only a few studies have been done on a ferromagnetic (FM) MnPt alloy, despite its higher magnetic moment than FePt. In this study, the effect of group VIII elements (Fe, Ru) on the thermodynamic, magnetic and vibrational properties of MnPt alloy is being investigated using density functional theory (DFT) based calculations. The heats of formation were found to increase with an increase in Fe and Ru compositions, indicating that the thermodynamic stability is not enhanced. It was also found that the ferromagnetic state is improved below 12.5 at. % Fe. The vibrational properties are estimated from the calculated phonon dispersion curves. Based on the results, these alloys would be suitable for the development of high-strength magnetic components in the future.